Upaya Pencegahan Stunting melalui Kegiatan Posyandu Desa Sungai Manau, Kecamatan Kuantan Mudik, Provinsi Riau - Naila Fauza; Faghas Prandima Augika; Ahmad Taufiq P.; Amdan Arfisan; Gega Arnanda; Anisa Herninandari; Lesti Hardianti; Mutia Mustika Rani; Nilam Sari; Viani Ghefira Deflides; Yola Gusmarinda (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Children aged five and under are included in the high-risk category for experiencing impaired growth and physical development if nutritional problems occur. Malnutrition and health problems that commonly occur in children include malnutrition, obesity, and below normal body posture or stunting. One of the efforts that can be made in early detection and prevention of stunting is through Posyandu activities. The University of Riau real work team took part in community service through routine toddler posyandu activities and conducted research to determine the level of knowledge of mothers of toddlers regarding stunting in Sungai Manau village. This service activity is in line with research which aims to find out and increase mother's knowledge about stunting. This activity uses the health education method for mothers with toddlers on August 9, 2022 at the Posyandu in Sungai Manau village. Through this activity it was found that the majority of mothers' knowledge regarding stunting was in the medium category (57%). During the evaluation, it was found that the majority of mothers could answer questions about stunting correctly. We hope that this service activity could be continued with different interventions such as the use of local food resources to overcome stunting in children.